A 3E typology of visitors at an electronic dance music festival. Issue 3 (10th October 2016) - Kruger, Martinette; Saayman, Melville
Abstract : Purpose: The purpose of this paper is to determine the motives of visitors to an electronic dance music (EDM) festival in South Africa and clustered the participants according to these motives. Design/methodology/approach: Based on a visitor survey at the oldest EDM festival in South Africa, namely, H2O, five motives for attending H2O were identified (fun and dance; novelty; excitement, group identity and entertainment; lifestyle and well-being; and travel and escape), while the results revealed three clusters of EDM festival visitors: enthusiasts, energizers and electros. The results demonstrated that clustering EDM festival visitors based on their motives is a useful market segmentation tool as it yields a clear and direct profile and understanding of different types of attendees and their preferences. Findings: The results as well as findings emphasize how EDM events can play a role in expanding tourism, especially youth travel, by hosting more EDM festivals in the country. Originality/value: The study proposes a 3E typology of EDM festival visitors that could be applied to other EDM festival and event markets. This research, therefore, makes a clear contribution to the literature on EDM festivals and events and the market that this distinct music genre attracts.